Computed Tomographic Evaluation of the Accuracy of Minimally Invasive Sacroiliac Screw Fixation in Cats - Wills, Daniel J.; Neville-Towle, Jack; Podadera, Juan; Johnson, Kenneth A. (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objectives The aim of this study was to report the use of computed tomography (CT) for postoperative evaluation of the accuracy of sacroiliac reduction and minimally invasive screw fixation in a series of five cats.Methods Medical records between January 2016 and March 2017 of cats presenting to the author's institution were reviewed. Included were cats that had undergone minimally invasive sacroiliac screw fixation with a complete medical record and pre- and postoperative radiographs. Screw size was obtained from the medical records. CT images were acquired prospectively and evaluated to assess joint reduction, relative screw size and screw positioning.Results Six sacroiliac luxations and 6 screws were available. Fixation was achieved with either a 2.4 (n = 1) or 2.7 mm (n = 5), 316L stainless steel, cortical bone screw. Mean screw size as a proportion of sacral diameter was 47.7%. Sacroiliac reduction >90% in the craniocaudal plane and sacral screw purchase >60% of the sacral width were achieved in 3/5 cases. Mean dorsoventral screw angulation was 1.6 degrees (range: −9.7 to 11.7 degrees) and craniocaudal angulation was −4.5 degrees (range: −16.6 to 6.6 degrees). Complications included screw loosening in the one case of bilateral repair and penetration of the neural canal in one case which was not detected with postoperative radiographic evaluation.Clinical Significance CT evaluation provides a useful method for the assessment of sacroiliac reduction and the accuracy of screw placement.
Keywords: sacroiliac luxation; computed tomography; cats; minimally invasive approach; screw fixation